2015
DOI: 10.4103/0253-7176.150848
|View full text |Cite
|
Sign up to set email alerts
|

Can Masturbatory Guilt Lead to Severe Psychopathology: A Case Series

Abstract: Masturbation is common in all societies. Despite being common, it is admonished culturally and almost all religions prohibit masturbation and consider it an act of immorality. The prohibition for masturbation leads to a lot of cultural beliefs, including certain myths, which influence sexual behavior of the person. The impact of these common cultural myths associated with masturbation, are clinically understood as Dhat syndrome and masturbatory guilt. Although there is a reasonable literature on Dhat syndrome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Others decided to move beyond the social boundaries governing female sexuality and sexual behavior, albeit their influence remained. This finding was somewhat opposite of what would be predicted of South Asian females given their limited access to sexual health knowledge, restricted sexual activity and sexual behavior as well as sexual guilt, anxiety and shame associated with South Asian cultures [67][68][69][70]. This may reflect the assimilation to mainstream (Canadian) culture.…”
Section: Discussionmentioning
confidence: 70%
“…Others decided to move beyond the social boundaries governing female sexuality and sexual behavior, albeit their influence remained. This finding was somewhat opposite of what would be predicted of South Asian females given their limited access to sexual health knowledge, restricted sexual activity and sexual behavior as well as sexual guilt, anxiety and shame associated with South Asian cultures [67][68][69][70]. This may reflect the assimilation to mainstream (Canadian) culture.…”
Section: Discussionmentioning
confidence: 70%
“…However, in our review of current evidence, we found both Koro and KS cases have been reported to be associated with urogenital pathology, anxiety, and psychosexual dysfunction. 79…”
Section: Discussionmentioning
confidence: 99%
“…Masturbation was associated with negative feelings as guilt (in 82%) or religious belief (in 73.4%). Aneja et al [20] described two cases of depression caused by masturbatory guilt. Greenberg and Archambault [21] found that guilty feelings connected with masturbation occurred in 40% of a sample of university students in USA.…”
Section: Discussionmentioning
confidence: 99%